Pollutant Removal Capability Of An Ecological Swale - Ashgul, Aishahturizdah (Universiti Sains Malaysia, 2005)
As development and impermeability increase in an area, it can have significant impact on hydrologic and hydraulic process as well as degradation of water quality on receiving waters. In order to solve the entire problem caused by the conventional drainage system, a new approach has been introduced to manage the storm water. Bio-Ecological Drainage system (BIOECODS) forms an alternative method based on control at source approach to manage storm water quality at USM Engineering campus, Nibong Tebal by using ecological swales and ecological pond. However this study only focuses on the capability of an ecological swale in terms of pollutant removal. A storm water quality monitoring at an ecological swale is being carried out by using sampling method. Samples are taken from upstream and downstream along ecological swale. And then, samples are analyzed in laboratory to identify the level of pollutant. Parameter analyzed in laboratory includes TSS, TP and Pb. Reduction in the concentration of pollutants from upstream to downstream show that ecological swale is very effective to remove pollutant. The performance of swales in term of pollutant removal diminished with increasing flow rate for TSS, due to the importance of physical process (sedimentation and filtration) in their removal. TP and Pb removal also decrease because of the increasing of flow rate.